A systematic review on botanical background, phytochemical and pharmacological properties of Nymphaea nouchali - Sarma, Himshikhar; Sahariah, Gunjan; Bharadwaj, Abhilash; Sharma, Dipjyoti; Porasar, Pollobi; Dutta, Koushik Nandan (Journal of Applied Pharmaceutical Research, 2024)
Background: Nymphaea nouchali is a widely distributed aquatic plant prevalent in tropical and subtropical areas, flourishing in freshwater habitats. It is widely recognized as the water lily. Historically, it has been utilized in several medical systems to address conditions such as diabetes, liver diseases, and urinary tract issues. The plant comprises several bioactive substances, including flavonoids, phenolic acids, and alkaloids, which enhance its therapeutic qualities. This review examines the botanical, phytochemical, and pharmacological characteristics of Nymphaea nouchali to evaluate its medicinal potential. Methodology: This review combines data from previous botanical, phytochemical, and pharmacological research on Nymphaea nouchali. The bioactive components extracted from the plant were examined for their therapeutic capabilities. The pharmacological effects, encompassing antibacterial, antioxidant, anti-inflammatory, antinociceptive, and anticancer properties, were assessed by several in vitro and in vivo experimental methods. Results: A phytochemical study identified the presence of substances, including nymphal, gallic acid, and quercetin. These chemicals are associated with notable biological functions. Alkaloids and tannins had antibacterial activities, but phenolic compounds and flavonoids showed potent antioxidant capabilities. The herb demonstrated antinociceptive properties. Initial investigations suggested possible anticancer effects on some cell lines; nevertheless, further study is required. Conclusion: Nymphaea nouchali shows significant pharmacological potential due to its many bioactive components. Although traditional medicinal usage supports its therapeutic benefits, further preclinical and clinical investigations are necessary to validate its efficacy and safety for pharmaceutical uses.